2020
DOI: 10.3390/cells9091951
|View full text |Cite
|
Sign up to set email alerts
|

A New ERAP2/Iso3 Isoform Expression Is Triggered by Different Microbial Stimuli in Human Cells. Could It Play a Role in the Modulation of SARS-CoV-2 Infection?

Abstract: Following influenza infection, rs2248374-G ERAP2 expressing cells may transcribe an alternative spliced isoform: ERAP2/Iso3. This variant, unlike ERAP2-wt, is unable to trim peptides to be loaded on MHC class I molecules, but it can still dimerize with both ERAP2-wt and ERAP1-wt, thus contributing to profiling an alternative cellular immune-peptidome. In order to verify if the expression of ERAP2/Iso3 may be induced by other pathogens, PBMCs and MDMs isolated from 20 healthy subjects were stimulated with flu, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…Aberrant isoform usage and splicing have previously been associated with the human antiviral response, cancer, and neurodegenerative diseases 64 – 66 ; moreover, a recent study found that SARS-CoV-2 infection alters isoform usage of the ERAP2 gene 67 . However, to our knowledge, ours is the first genome-wide analysis of the effect of SARS-CoV-2 on isoform usage.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant isoform usage and splicing have previously been associated with the human antiviral response, cancer, and neurodegenerative diseases 64 – 66 ; moreover, a recent study found that SARS-CoV-2 infection alters isoform usage of the ERAP2 gene 67 . However, to our knowledge, ours is the first genome-wide analysis of the effect of SARS-CoV-2 on isoform usage.…”
Section: Discussionmentioning
confidence: 99%
“…rs2248374A allele gives normal ERAP2 protein expression, whereas rs2248374G produces unstable mRNA degraded by nonsense mediated decay and usually results in undetectable protein expression (56). However, it has been reported recently that during stimulation by microbial infections the rs2248374G allele may give two truncated protein isoforms absent in rs2248374AA homozygotes and with an unknown biological role (57)(58)(59), possibly interfering in ERAP1 activity. Why the haplotype GCTCCG without functional ERAP2 molecule gives opposite results in never-smokers versus smokers, whereas the same ERAP1 (GCTCCA) with functional ERAP2 does not affect NSCLC prevalence in any of these groups, is not clear.…”
mentioning
confidence: 99%
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] ...…”
Section: Uncited Referencesunclassified